Children's Understanding of Area of Rectangular Regions and Volumes of Rectangular Shapes and the Relationship of These Measures to Their Linear Dimensions - Martin, Joan D. (Tufts Archival Research Center, 2005)
A qualifying paper submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Math, Science, Technology, and Engineering Education. Abstract: What is needed to strengthen our students' understanding of the attributes of space, to prepare our students for a world that requires increasingly advanced levels of technical sophistications? Again the questions posed are: which concepts should be taught and when should these concepts be introduced? Are there particular sequences or an order in which these concepts should be taught? And what materials and tools should be used in the teaching and learning of geometry? In seeking to answer the above questions, this paper focuses on a narrower band of geometric measurement, aimed at harvesting the findings of the reviewed research and suggesting fruitful possibilities for further study. The main goal is to review the literature on studies that have been conducted specifically in the treatment of area and volume, as well as length, with elementary students.